High Harmonic Spectroscopy of the Cooper Minimum in Molecules - Wong, M. C. H.; Le, A.-T.; Alharbi, A. F.; Boguslavskiy, A. E.; Lucchese, R. R.; Brichta, J.-P.; Lin, C. D.; Bhardwaj, V. R. (My University, 2013)
The Cooper minimum (CM) has been studied using high harmonic generation solely in atoms. Here, we present detailed experimental and theoretical studies on the CM in molecules probed by high harmonic generation using a range of near-infrared light pulses from λ=1.3 to 1.8 μm. We demonstrate the CM to occur in CS2 and CCl4 at ∼42 and ∼40 eV, respectively, by comparing the high harmonic spectra with the known partial photoionization cross sections of different molecular orbitals, confirmed by theoretical calculations of harmonic spectra. We use CM to probe electron localization in Cl-containing molecules (CCl4, CH2Cl2, and trans-C2H2Cl2) and show that the position of the minimum is influenced by the molecular environment.